Domain size effects in neutron and SR powder diffraction studies of some oxides - Przeniosło, R.; Sosnowska, I.; Żółtek, M.; Wroblewski, T.; Shiojiri, M.; Hohlwein, D.; Troyanchuk, I.O. (Journal of Alloys and Compounds, 1999)
We discuss the properties of synchrotron radiation (SR) and neutron powder diffraction investigations of the crystal and magnetic structure of solids. Special emphasis is paid to the analysis of the full width at half maximum (FWHM) of the observed Bragg reflections and its relation with the size of the coherently ordered regions of the material. Two specific examples are discussed: a SR powder diffraction study of the crystal structure of the hexaferrite BaSn 2Fe 4O 11 and a neutron powder diffraction study of the magnetic ordering of the magnetic moments of manganese ions in the distorted perovskite system CaMn 7O 12.